2014
DOI: 10.1002/bmc.3377
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological screening of human plasma by on‐line SPE‐HPLC‐DAD: identification and quantification of basic drugs and metabolites

Abstract: An automated multi-analyte screening method for the identification and quantification of 92 drugs and metabolites based on on-line solid-phase extraction-high-performance liquid chromatography-diode array detection technique was developed and successfully validated. In addition, a database with 870 entries including UV-spectra, relative/retention times and response factors of toxicologically relevant compounds was created. Plasma samples (0.2 mL) were treated with methanol, diluted with buffer and on-line extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…The values were in the range of 0.5 and 20 ng mL −1 . These results were considered more significant than the values reported by Steuer et al and Sempio et al In our study, we determined that LLOQs for whole blood ranged from 0.5 to 10 ng mL −1 for benzodiazepines and antidepressants, while Mut et al reported values of 40 ng mL −1 . The LLOQs in urine analysis were considered adequate for all analytes once the RSD (%) was lower than 15%.…”
Section: Resultssupporting
confidence: 42%
“…The values were in the range of 0.5 and 20 ng mL −1 . These results were considered more significant than the values reported by Steuer et al and Sempio et al In our study, we determined that LLOQs for whole blood ranged from 0.5 to 10 ng mL −1 for benzodiazepines and antidepressants, while Mut et al reported values of 40 ng mL −1 . The LLOQs in urine analysis were considered adequate for all analytes once the RSD (%) was lower than 15%.…”
Section: Resultssupporting
confidence: 42%
“…(b). The following drugs and metabolites concentrations were determined in the patient's plasma sample, quantified using the method described elsewhere (Mut et al ., ): analyte [concentration in mg/L, upper or therapeutic concentration (range) in mg/L], nordazepam (0.17, 0.02–0.8), diazepam [positive <LOQ (0.04), 0.13–0.4], lorazepam [positive <LOQ (0.05), 0.02–0.25], 4‐methylaminoantipyrine and an active metabolite of metamizole (39.8, 5.00); and [concentration in mg/L, below therapeutic concentration (range) in mg/L], quetiapine (0.06, 0.10–050) and duloxetine [positive <LOQ (0.04), 0.03–0.12]. Additionally, codeine was identified qualitatively.…”
Section: Resultsmentioning
confidence: 97%
“…The on-line SPE-HPLC-DAD model was similar to prior approaches (Grobosch et al, 2009;Mut et al, 2011Mut et al, , 2015. For on-line SPE the following eluents were used: A (acetonitrile-water, 90:10, v/v) as the mobile phase, E (0.01 M potassium dihydrogen phosphate buffer, pH 6) for loading and equilibration and D (water) for rinsing and purging of the SPE column.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations